The indicated function y1(x)
is a solution of the associated homogeneous equation. Use the method of reduction of order to find a second solution y2(x)
of the homogeneous equation and a particular solution yp(x)
of the given nonhomogeneous equation.
y'' + y' = 1; y1 = 1
y2(x)
= yp(x)
=
Solution
"y'' + y' = 1"
"{d^2y\\over dx^2}+{dy\\over dx}=1"
First, reduce the differential equation to first order
Let "z={dy\\over dx} \\implies {dz\\over dx}={d^2y\\over dx^2}"
Substituting to differential equation, we have
"{dz\\over dx}+z=1"
"{dz\\over dx}=1-z"
Do reciprocal on both sides of the differential equation
"{1\\over 1-z}={dx\\over dz}"
Multiply both sides of the differential equation by "dz" to get
"{dz\\over 1-z}=dx"
Integrate both sides
"\\int{dz\\over 1-z}=\\int dx"
"\\implies -ln(1-z)=x+C"
"\\implies ln(1-z)=-x+C"
Introduce exponential on both sides
"e^{ln(1-z)}=e^{-x+c}"
"\\implies 1-z=e^{-x+C} \\implies z=1-e^{-x+C}=1-Ce^{-x}"
But "z={dy\\over dx}"
"\\implies {dy\\over dx}=1-Ce^{-x}"
Multiply both sides of the differential equation by "dx"
"\\implies dy=(1-Ce^{-x})dx"
Integrate both sides
"\\int dy=\\int (1-Ce^{-x})dx"
"\\implies y=x+C_1e^{-x}+C_2"
"\\therefore y_2(x)=e^{-x}" and "y_p(x)=x"
Comments
Leave a comment